Al-Hajjaj's Strategies in Surat Al-Rum: A Linguistic Argumentative Study in The Holy Qur'an - Nadia Lotfy Nasser (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
The Holy Surah included dialectical methods, such as the argumentative strategy that achieves persuasion through linguistic mechanisms and the argumentative ladder, according to Oswald Decro's theory of linguistic arguments. The importance of this research is that it sheds light on the ability of the linguistic mechanisms in Surat Al-Rum to achieve the argumentative function and influence the recipient. The main question of the research is whether the linguistic and rhetorical mechanisms and the argumentative scale achieved the argumentative function and affected the recipient? The approach that the research follows is descriptive and analytical, as it follows the approach of the linguistic arguments’ theory of "Oswald Decro" and "Unscomber". The linguistic strategies in general, the argumentative ladder, and the argumentative links, have achieved an impact on the recipient, with the huge potential argumentative potentials that the linguistic and rhetorical structures bear in them. The power of linguistic, rhetorical and semantic casting in the surah also represented the power of the speaker, who is the Creator Almighty. The research is new in that it sheds light on the power of linguistic and rhetorical casting and the argumentative scale, which achieved strong argumentative energies that affect the recipient in temporal and spatial permanence.